1959
DOI: 10.1002/jcp.1030540419
|View full text |Cite
|
Sign up to set email alerts
|

The active site of esterases

Abstract: This paper presents data from our laboratory pertaining to the chemical structure of the active site of a group of esterases. We attempted to frame these into a general pattern in agreement with wellestablished knowledge in this field. First we should specify that the term "active site" will refer to those regions of the enzyme surface where the substrate is localized and activated during the enzymic action.Knowledge of the structure of the active site of esterases is based on indirect evidence mostly obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1961
1961
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…The conditions were also designed to eliminate any significant effect of "ageing" on the quantitative results by keeping the time lapse between the DFP and the 2-PAM incubation to <1 h. ("Ageing" is a process whereby dealkylation of the organophosphorous inhibited enzymes occurs with time and prevents reactivation by 2-PAM. The accumulated evidence from several studies [5,9,11,14,21,22,23] leads to the conclusion that the half-life for ageing of AChe inactivated with DFP is longer than for butyrylcholinesterase (BuChe), is on the order of 10-35 h at room temperature, and is temperature-dependent. )…”
Section: Methodsmentioning
confidence: 99%
“…The conditions were also designed to eliminate any significant effect of "ageing" on the quantitative results by keeping the time lapse between the DFP and the 2-PAM incubation to <1 h. ("Ageing" is a process whereby dealkylation of the organophosphorous inhibited enzymes occurs with time and prevents reactivation by 2-PAM. The accumulated evidence from several studies [5,9,11,14,21,22,23] leads to the conclusion that the half-life for ageing of AChe inactivated with DFP is longer than for butyrylcholinesterase (BuChe), is on the order of 10-35 h at room temperature, and is temperature-dependent. )…”
Section: Methodsmentioning
confidence: 99%
“…Eisen, 1962;Day et al, 1962;Nisonoff and Pressman, 1958). The question arises: do those Ab sites which are most rapidly labeled with a HpX reagent show the largest K , values for the reversible reaction with Hp?…”
Section: The Heterogeneity Of Ab-active Sitesmentioning
confidence: 99%
“…Kinetic studies (17,18) and direct chemical evidence (19) support the hypothesis that the essential basic group of esterases (pK, 6-7) is the in~idazole ring of histidine. The consistent isolation s f labelled serine phosphate derivatives from esterases after their inhibition by organophosphorus coinpounds (20) has provided strong evidence that serine is associated with the active site. On the basis of his pH-activity data and observations with T E P P and BFP, Fitch (4) concluded that neither histidine nor serine were likely to be of importance in the activities of the bacterial cholinesterase.…”
Section: Discussionmentioning
confidence: 98%